Triggering the decision to undergo medical male circumcision: a qualitative study of adult men in Botswana. Issue 8 (2nd August 2016) - Wirth, Kathleen E.; Semo, Bazghina-werq; Ntsuape, Conrad; Ramabu, Nankie M.; Otlhomile, Boyce; Plank, Rebeca M.; Barnhart, Scott; Ledikwe, Jenny H.
ABSTRACT: In 2007, the World Health Organization endorsed voluntary medical male circumcision (VMMC) as part of comprehensive HIV-prevention strategies. A major challenge facing VMMC programs in sub-Saharan Africa remains demand creation; there is urgent need for data on key elements needed to trigger the decision among eligible men to seek VMMC. Using qualitative methods, we sought to better understand the circumcision decision-making process in Botswana related to VMMC. From July to November 2013, we conducted 27 focus group discussions in four purposively selected communities in Botswana with men (stratified by circumcision status and age), women (stratified by age) and community leaders. All discussions were facilitated by a trained same-sex interviewer, audio recorded, transcribed and translated to English, and analyzed for key themes using an inductive content analytic approach. Improved hygiene was frequently cited as a major benefit of circumcision and many participants believed that cleanliness was directly responsible for the protective effect of VMMC on HIV infection. While protection against HIV was frequently noted as a benefit of VMMC, the data indicate that increased sexual pleasure and perceived attractiveness, not fear of HIV infection, was an underlying reason why men sought VMMC. Data from this qualitative study suggest that more immediate benefits of VMMC, such as improved hygiene and sexual pleasure, play a larger role in the circumcision decision compared with protection from potential HIV infection. These findings have immediate implications for targeted demand creation and mobilization activities for increasing uptake of VMMC among adult men in Botswana.